Experimental evaluation of self-sensing cement-based composites with carbon nanofillers for Structural Health Monitoring of fire-damaged structures - Nalon, Gustavo Henrique (2020)
The deeper understanding of the electrical properties of cement-based materials and the recent knowledge on Nanoscience and Nanotechnology allowed the development of smart pastes, mortars and concretes with intrinsic strain sensing and damage detection properties. Since fire is one of the most severe threats to the structural integrity of concrete elements, the reuse of fire-damaged structures requires an accurate diagnosis of their damage level and residual structural performance. In this work, an experimental evaluation of innovative technologies for Structural Health Monitoring of fire-damaged concrete elements was developed: self-sensing cement-based composites containing multi-walled carbon nanotubes (MWCNT) or carbon-black nanoparticles (CBN). Microstructure, residual mechanical properties and sensing ability of different composites exposed to temperatures of 200 ºC, 400 ºC and 600 ºC were investigated. The effects of rehydration after fire exposure on these parameters were also studied. Composites with an intrinsic ability to measure strain and detect damage after exposure to temperatures up to 600 ºC were developed. They also exhibited an interesting ability of detection of damage recovery due to the post-fire rehydration. Keywords: Structural Health Monitoring. Nanomodified cementitious materials. Post-fire structural behavior. Self-sensing composites.